2022
DOI: 10.1302/2633-1462.31.bjo-2021-0051.r1
|View full text |Cite
|
Sign up to set email alerts
|

Cefazolin remains the linchpin for preventing acute periprosthetic joint infection following primary total knee arthroplasty

Abstract: Aims Despite recent literature questioning their use, vancomycin and clindamycin often substitute cefazolin as the preoperative antibiotic prophylaxis in primary total knee arthroplasty (TKA), especially in the setting of documented allergy to penicillin. Topical povidone-iodine lavage and vancomycin powder (VIP) are adjuncts that may further broaden antimicrobial coverage, and have shown some promise in recent investigations. The purpose of this study, therefore, is to compare the risk of acute periprosthetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Wyles et al [ 5 ] found higher rates of PJI when non-cephalosporin prophylactic antibiotics were used following primary TKA and THA. Buchalter et al [ 12 ] also reported a significantly higher PJI rate after TKA in a non-cephalosporin cohort in their hospital. Nationwide research from Wu et al [ 10 ] did not observe any significant differences in PJI rate between a cephalosporin and non-cephalosporin cohort after THA; they did however report a significant difference in PJI rate after TKA and after shoulder arthroplasty.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Wyles et al [ 5 ] found higher rates of PJI when non-cephalosporin prophylactic antibiotics were used following primary TKA and THA. Buchalter et al [ 12 ] also reported a significantly higher PJI rate after TKA in a non-cephalosporin cohort in their hospital. Nationwide research from Wu et al [ 10 ] did not observe any significant differences in PJI rate between a cephalosporin and non-cephalosporin cohort after THA; they did however report a significant difference in PJI rate after TKA and after shoulder arthroplasty.…”
Section: Discussionmentioning
confidence: 92%
“…There are some studies to date that have analyzed the influence of different prophylactic antibiotic regimens on PJI rates after arthroplasty surgery [ 22 , 23 , 24 , 25 , 26 ]. However, not many have compared different prophylactic antibiotic regimens adjusted due to reported penicillin or cephalosporin allergy [ 5 , 8 , 10 , 12 , 13 ]. Wyles et al [ 5 ] found higher rates of PJI when non-cephalosporin prophylactic antibiotics were used following primary TKA and THA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Muwanis et al found that dilute povidone-iodine (Betadine, Avrio Health L.P, Stamford, CT, USA) compared with normal saline irrigation is an economical and simple technique to reduce PJI and more specifically SSI in TKA [ 57 ]. According to Buchalter et al, in spite of the utilization of topical irrigation solutions and addition of local antimicrobial agents, the use of a non-cephalosporin perioperative antibiotic (either vancomycin or clindamycin) is related to a higher risk of TKA PJI compared with cefazolin [ 58 ]. An increased frequency of PJI in individuals experiencing mobilization under anesthesia (MUA) was reported by Parkulo et al [ 59 ].…”
Section: Discussionmentioning
confidence: 99%